AB1138 BONE SARCOIDOSIS: USEFULNESS OF 18F-FDG PET/CT. (June 2019) - Demaria, Lucie; Borie, Raphael; Benali, Khadija; Forien, Marine; Dieudé, Philippe; Crestani, Bruno; Ottaviani, Sebastien
Abstract : Background: Bone sarcoidosis: usefulness of 18 F-FDG PET/CT Objectives: Bone sarcoidosis is usually rare but more sensitive imaging procedures such as 18 F-fluorodeoxyglucose Positron Emission Tomography/Computed Tomography ( 18 F-FDG PET/CT) allow a better characterization of such lesions. We aimed to describe bone sarcoidosis involvement using 18 F-FDG PET/CT. Methods: We performed an observational retrospective study of patients with pulmonary sarcoidosis having a 18 F-FDG PET/CT. As stated by ATS/ERS/WASOG criteria, diagnosis of sarcoidosis was established on the presence of clinical symptoms and/or imaging features of sarcoidosis, and evidence of non-caseating epithelioid granuloma in a biopsy sample after exclusion of other known etiology of granuloma. We assessed clinical and 18 F-FDG PET/CT characteristics. Results: A total of 85 patients (56.5% of female, median age 47 years) with sarcoidosis were analyzed. The median of disease follow-up was 4 years. Sarcoidosis occurred in more than three organs among 66% of cases. Using ATS/ERS/WASOG criteria, bone sarcoidosis was diagnosed in 12 (14%) patients. Spine was the most commonly affected bone (92%), followed by pelvis (67%), sternum (33%), humerus (25%) and fingers (17%). Only peripheral adenopathy was associated with bone lesions ( p =0.04). Seven patients have benefited from a follow-up 18 F-FDG PET/CT, which in 100% of cases showed an improvement of lesions. Conclusion: Bone sarcoidosis occurred in 14% of patients, affecting multiple bones and mostly the axial skeleton. 18 F-FDG PET/CT appears to be a sensitive imaging for diagnosis and follow-up of bone sarcoidosis. References: [1] Aberg C, and al. AJR Am J Roentgenol. avr 2004 [2] Baldini S, and al. Br. J. Haematol. nov 2008 [3] Bechman K, and al. Rheumatology 1 mai 2018 [4] ClarenÇon F, and al. Spine. 15 sept 2007 [5] Conte G, and al. Ecancermedicalscience. 7 mai 2015 [6] Costabel U, and al. European Respiratory Society. World Association for Sarcoidosis and Other [7] Granulomatous Disorders. European Respiratory Journal. 1 oct 1999 [8] Glaudemans AWJM, and al. Journal of Immunology Research. 2013 [9] Grozdic Milojevic I, and al. Sarcoidosis Vasc Diffuse Lung Dis. 29 mars 2016 [10] James DG, and al. Ann. N. Y. Acad. Sci. 1976 [11] Judson MA, and al. Sarcoidosis Vasc Diffuse Lung Dis. 18 avr 2014 [12] Kaira K, and al. Chest. avr 2007 [13] Lefere M, and al. Clin Nucl Med. mars 2003 [14] Mostard RL, and al. Clin Nucl Med. janv 2012 [15] Prost N de, and al. RES. 2010 [16] Sparks JA, and al. Seminars in Arthritis and Rheumatism. 1 déc 2014 [17] Thelier N, and al.J. Rheumatol. août 2008 [18] Wilcox A, and al. Current Opinion in Rheumatology. juill 2000 [ [19] Zhou Y, and al. Seminars in Arthritis and Rheumatism. 1 févr 2017 [20] Zisman DA, and al. Semin Respir Crit Care Med. déc 2002 Disclosure of Interests: None declared